Penerapan Model Pembelajaran Kooperatif Teknik Kancing Gemerincing untuk Meningkatkan Aktivitas Siswa - Muhaiminul Azizah; Syifaul Gummah; Baiq Azmi Sukroyanti (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2019)
[Title: The Implementation of the Cooperative Learning Model with Jingle Button Techniques to Increase Student Activities]. This study aims to improve the learning activities of students of class VIII Madrasah Tsanawiyah (MTs) NW SIKUR by applying cooperative learning models of clanging button techniques. This type of research is a classroom action research conducted in 2 cycles. The subjects in this study were students of class VIII MTs NW SIKUR, amounting to 37 people. Student and teacher learning activity data is collected through observation sheets. From the results of the study, it was found that the total score of student activity in the 2 cycles always increased. In cycle, I the score of student activity was 2.88 with the category of quite active while in cycle II the score of student activity was 3.41 with the active category. Based on the overall results of this study it can be concluded that the application of the clanking button learning cooperative model can increase the learning activities of students of class VIII Madrasah Tsanawiyah NW SIKUR in the academic year 2017/2018.